2011
DOI: 10.1007/s11060-011-0594-5
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic and predictive value of epigenetic silencing of MGMT in patients with high grade gliomas: a systematic review and meta-analysis

Abstract: Epigenetic silencing of the O(6)-methylguanine-DNA methyltransferase (MGMT) gene is associated with improved survival in patients with high-grade gliomas (HGG), with varying estimates of magnitude. The objective of this meta-analysis is to determine the prognostic value of MGMT silencing, and assess its predictive value by treatment type. MEDLINE and EMBASE databases were searched for studies relating to gliomas and MGMT. Studies reporting overall survival (OS) by MGMT status in patients with HGG were consider… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 36 publications
1
45
0
2
Order By: Relevance
“…Methylation of the O 6 -methylguanine-DNA methyltransferase (MGMT) promoter is found in about 45% of GBMs occurring in adult patients, causing impaired DNA repair in response to alkylating agents such as temozolomide (150)(151)(152)(153)(154)(155)(156)(157). MGMT promoter methylation is therefore used as a biomarker to predict responsiveness to temozolomide (153,154,157,158). However, both the frequency and the predictive value of MGMT silencing in pediatric HGGs remain controversial, even after collectively more than 1000 children with HGG have been treated with temozolomide in multicenter trials (159)(160)(161)(162).…”
Section: High-grade Gliomasmentioning
confidence: 99%
“…Methylation of the O 6 -methylguanine-DNA methyltransferase (MGMT) promoter is found in about 45% of GBMs occurring in adult patients, causing impaired DNA repair in response to alkylating agents such as temozolomide (150)(151)(152)(153)(154)(155)(156)(157). MGMT promoter methylation is therefore used as a biomarker to predict responsiveness to temozolomide (153,154,157,158). However, both the frequency and the predictive value of MGMT silencing in pediatric HGGs remain controversial, even after collectively more than 1000 children with HGG have been treated with temozolomide in multicenter trials (159)(160)(161)(162).…”
Section: High-grade Gliomasmentioning
confidence: 99%
“…The most complete and most durable responses to temozolomide and the longest overall survival times are seen in the subgroup of tumors with epigenetic silencing of the MGMT enzyme that normally repairs the cytotoxic O 6 -methylguanine (O 6 -MeG) DNA adducts induced by temozolomide (3). However, MGMT methylation status does not correlate with temozolomide sensitivity in all patients, and thus MGMT expression is insufficient to explain temozolomide resistance in all tumors (1,3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, it is reasonable to surmise that the prognosis of patients with mutant IDH1 might be favorable. MGMT promoter methylation has been reported as a favorable prognostic factor for survival and a predictive marker for benefit from alkylating agent chemotherapy in patients with GBM (Hegi et al, 2005;Stupp et al, 2009;Olson et al, 2011). It is also found that tumors with methylated MGMT promoter has longer PFS when treated with RT plus chemotherapy compared with patients treated with RT alone (Wick et al, 2013).…”
Section: Discussionmentioning
confidence: 98%